2019
DOI: 10.1021/acs.jafc.9b00816
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms and Biochemical Markers As Complementary Tools To Characterize Hops (Humulus lupulus L.) in Brewing Practice

Abstract: In brewing practice, the use of the appropriate hop variety is essential to produce consistent and high-quality beers. Yet, hop batches of the same variety cultivated in different geographical regions can display significant biochemical differences, resulting in specific taste- and aroma-related characteristics in beer. In this study, we illustrate the complementarity of genetic and biochemical fingerprinting methods to fully characterize hop batches. Using genotyping-by-sequencing (GBS), a set of 1 830 polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 48 publications
(107 reference statements)
2
18
0
Order By: Relevance
“…In our previous research ( 18, 19 ) , biochemical dissimilarities were found between Amarillo hops cultivated in Idaho or Washington, and between Cascade hops cultivated in Australia, Germany, or Washington. The bitter acids and essential oil content, and especially the composition of the oils, were affected by the geographical region where the two hop varieties were cultivated.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…In our previous research ( 18, 19 ) , biochemical dissimilarities were found between Amarillo hops cultivated in Idaho or Washington, and between Cascade hops cultivated in Australia, Germany, or Washington. The bitter acids and essential oil content, and especially the composition of the oils, were affected by the geographical region where the two hop varieties were cultivated.…”
Section: Introductionmentioning
confidence: 84%
“…True‐to‐type hop samples, confirmed using DNA fingerprinting ( 19 ) , of three widely used hop varieties were investigated: ‐Amarillo (‘VGXP01’) is an American hop variety introduced in 2003 by Virgil Gamache Farms Inc., Toppenish, Washington ( 33 ) . Amarillo is resistant to most common hop diseases and enjoys worldwide appreciation as a dual‐purpose variety conferring both aromatic as well as bittering qualities to beer ( 18, 34 ) . ‐Cascade was released in 1972 and has been the most popular hop variety among craft brewers for a number of years ( 34 ) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations